Ubiquitin ligase Nedd4 promotes α-synuclein degradation by the endosomal–lysosomal pathway - Tofaris, George K. (National Academy of Sciences, 2011)
α-Synuclein is an abundant brain protein that binds to lipid membranes and is involved in the recycling of presynaptic vesicles. In Parkinson disease, α-synuclein accumulates in intraneuronal inclusions often containing ubiquitin chains. Here we show that the ubiquitin ligase Nedd4, which functions in the endosomal–lysosomal pathway, robustly ubiquitinates α-synuclein, unlike ligases previously implicated in its degradation. Purified Nedd4 recognizes the carboxyl terminus of α-synuclein (residues 120–133) and attaches K63-linked ubiquitin chains. In human cells, Nedd4 overexpression enhances α-synuclein ubiquitination and clearance by a lysosomal process requiring components of the endosomal-sorting complex required for transport. Conversely, Nedd4 down-regulation increases α-synuclein content. In yeast, disruption of the Nedd4 ortholog Rsp5p decreases α-synuclein degradation and enhances inclusion formation and α-synuclein toxicity. In human brains, Nedd4 is present in pigmented neurons and is expressed especially strongly in neurons containing Lewy bodies. Thus, ubiquitination by Nedd4 targets α-synuclein to the endosomal–lysosomal pathway and, by reducing α-synuclein content, may help protect against the pathogenesis of Parkinson disease and other α-synucleinopathies.